Comparison of different stylets used for intubation with the C-MAC D-Blade® Videolaryngoscope: a randomized controlled study - Ömür,Dilek (2017)
Abstract Objective The angle of the C-MAC D-Blade® videolaryngoscope, which is used for difficult airway interventions, is not compatible with routinely used endotracheal tubes. Methods A prospective randomized crossover study was performed comparing five intubation methods for use with standardized airways, including using different stylets or no stylet: Group HS, hockey-stick stylet; Group DS, D-blade type stylet; Group CS, CoPilot® videolaryngoscope rigid stylet®; Group GEB, gum elastic bougie; and Group NS, no stylet. A manikin was used to simulate difficult intubation with a Storz C-MAC D-Blade® videolaryngoscope. The duration of each intubation stage was evaluated. Results Participants in this study (33 anesthesiology residents and 20 anesthesiology experts) completed a total of 265 intubations. The number of attempts made using no stylet was significantly greater than those made for the other groups (p < 0.05 for group NS- group GEB, group NS- group DS, group NS- group CS and group NS- group HS). The duration to pass the vocal cords significantly differed among all groups (p < 0.001). The total intubation duration was shortest when using D-blade stylet, CoPilot stylet and hockey stick stylet. Although no difference was observed between stylet groups, a significant difference was found between each of these three and no stylet and gum elastic bougie (p < 0.05 and p < 0.001, respectively). Conclusion Use of the correct stylet leads to a more efficient use of the Storz C-MAC D-Blade®. In our study, the use of the D-blade stylet, the CoPilot stylet and the hockey stick stylet provided quicker intubation, allowed easier passage of the vocal cords, and decreased the total intubation duration. To confirm the findings of our study, randomized controlled human studies are needed.